Epidemiological clinical characteristics of the Guillain Barré syndrome in patients attended in the Hospital Nacional Almanzor Aguinaga Asenjo 2012 – 2018 - Chunga-Vallejos, Enrique (2020)
Objective: To describe the epidemiological and clinical characteristics of Guillain Barré Syndrome in patients treated at the Hospital Nacional Almanzor Aguinaga Asenjo 2012 - 2018. Material and methods: Descriptive, retrospective study. We reviewed 103 medical records of patients diagnosed with Guillain-Barré Syndrome at the Hospital Nacional Almanzor Aguinaga Asenjo 2012 - 2018. A data collection form for each patient was used as an instrument, using as a base the Epidemiological Clinical Investigation Surveillance form the Guillain Barré Syndrome of Social Security EsSalud. Results: The majority were male (63.5%), the age group between 40 and 60 years predominated (45.6%). The majority of the cases studied came from Lambayeque (43.7%) and Cajamarca (40.8%). The characteristic motor symptom of Guillain-Barré Syndrome is muscle weakness (80.8%). The clinical variant was not determined in 60%. The majority of patients presented improvement or was cured (81%) Conclusions: The clinical epidemiological characteristics of Guillain Barré syndrome, present in a higher frequency the male sex and the predominant motor symptom: muscular weakness, in addition there was a notable increase in the incidence of cases per year, from 2016.